The enzyme activities of Caf1 and Ccr4 are both required for deadenylation by the human Ccr4-Not nuclease module - Maryati, Marayti; Airhihen, Blessing; Winkler, G. Sebastiaan (Portland Press, 2015)
In eukaryotic cells, the shortening and removal of the poly(A) tail (deadenylation) of cytoplasmic mRNA is a key event in regulated mRNA degradation. A major enzyme involved in deadenylation is the Ccr4-Not deadenylase complex, which can be recruited to its target mRNA by RNA-binding proteins or the miRNA repression complex. In addition to six non-catalytic components, the complex contains two enzymatic subunits with ribonuclease activity: Ccr4 and Caf1 (Pop2). In vertebrates, each deadenylase subunit is encoded by two paralogues: Caf1, which can interact with the anti-proliferative protein BTG2, is encoded by CNOT7 and CNOT8, while Ccr4 is encoded by the highly similar genes CNOT6 and CNOT6L. Currently, it is unclear whether the catalytic subunits work cooperatively, or whether the nuclease components have unique roles in deadenylation. We therefore developed a method to express and purify a minimal human BTG2-Caf1-Ccr4 nuclease sub-complex from bacterial cells. By using chemical inhibition and well-characterised inactivating amino acid substitutions, we demonstrate that the enzyme activities of Caf1 and Ccr4 are both required for deadenylation in vitro. These results indicate that Caf1 and Ccr4 cooperate in mRNA deadenylation and suggest that the enzyme activities of Caf1 and Ccr4 are regulated via allosteric interactions within the nuclease module.